Pelatihan Pembuatan Sabun Cuci Tangan Dari Minyak Jelantah Untuk Menumbuhkan Kesadaran Lingkungan dan Kreativitas Siswa - Enjeli Putri Amisani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Improper management of used cooking oil has a negative impact on the environment and health. This issue prompted students from the Special Mission Community Service Program at UIN Walisongo Semarang to collaborate with students from IAKN Palangka Raya in finding a solution. Students from the Special Mission Community Service Program conducted a training session on making hand soap from used cooking oil, attended by 20 sixth-grade students from SDN Wilayu Village, Wonosobo. The training aimed to foster environmental awareness and creativity among the students. During the training, the students guided the participants in the practical process of making soap. Additionally, they educated the students about the dangers of used cooking oil and its negative impacts on health and the environment. To ensure the students could replicate the process at home, the students created and uploaded a tutorial video on YouTube. Starting with the sixth-grade students at Wilayu Elementary School, the Special Mission Community Service Program students hope this initiative will have a positive impact on Indonesia's future.